Indigenous Communication System in Kokana Tribes - J. M. Gavit , M. C. Ahire and S. H. Ban (Indian Journal of Extension Education, 2013)
The study was conducted in tribal villages from Surgana tehsil of Nasik District of Maharashtra state. The data werecollected from 120 respondents. Majority of the Kokana tribes belonged to the age group of 45 years and above. More thanth one-third (35.00 %) of the Kokana tribes were educated up to pre-primary level i.e. up to 4 standard. Maximum familiesof Kokana tribe's had agriculture as main occupation and having annual income between ` 50,001/- to `1.00,000/-. Mostof them possessed medium size of land holding i.e. up to 1.01 to 2.00 ha. They had nuclear family type and medium sizedfamily i.e. 5 to 6 members. They had medium level of participation in any social organisation. Regarding indigenouscommunication systems cent per cent Kokana tribes knew about their traditional Kokana dance, and performed during themarriage ceremony.Cent per cent of them sang their traditional spiritual songs during Dongerdev festival, Avasar festivaland Navratra festival for community, personal health and personal aim (Navas).Most of the Kokana tribe knows about thegovernment schemes like Paryavaran Santulan Yojana, Village water Supply Scheme, Sarva ShikSha Abhiyan, GaonTanta Mukti Abhiayan, Jal Swaraj Prakalp, Watershed development programme, National Horticulture Mission, NationalRural Health Mission and Zilla Parishad schemes which are running in the village